Respon pertumbuhan dan produksi tanaman sawi Pakcoy (Brassica chinensis L.) akibat pemberian berbagai jenis pupuk kandang - Rahmadun Barokah; Sumarsono Sumarsono; Adriani Darmawati (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2017)
The purpose of this research was to determine growth and production responses of Spoon Mustard (Brassica chinensis L.) due to the treatment of various type of manure and to determine types of manure which effective for the growth and production of Spoon Mustard. This Research has been conducted at Experimental field and Laboratory of Plants’s Ecology and Production, Faculty of Animal and Agricultural Science, Diponegoro University from January to March 2017. This research used monofactorexperiment in Completely Randomized design arrangement. The treatment was variation of manure which were cow manure, goat manure, sheep manure, horse manure, and chicken manure, they would be compared with nontreatment (0 fertilizer) and 300 kg/ha urea in four times replication. The obtained data were processed statistically with analysis of variance (F test) and Duncan Multiple Range Test at 5% level. The result’s showed that manure treatment with different types gave effect to the plant heigh, number of leaves, leaf area, and plant production. The best treatment was chicken manure treatment which produced average of plant height as 26,33 cm, average of number of leaves as 11sheet, average of leaf area as 1033,30 cm, and Spoon Mustard production as 2319,90 g/m2.Keywords: Organic Fertilizer, Manure, Pakcoy.